Prospective cohort study to investigate the burden and transmission of acute gastroenteritis in care homes: epidemiological results. Issue 12 (8th December 2019) - Inns, Thomas; Pulawska-Czub, Anna; Harris, John P; Vivancos, Roberto; Beeching, Nicholas J; Iturriza-Gomara, Miren; O'Brien, Sarah J
Abstract : Objectives: To estimate the incidence of gastroenteritis in individuals in care homes. Design: Prospective cohort study. Setting: Five participating care homes in North West England, UK. Participants: Residents and staff present at the five study care homes between 15 August 2017 and 30 May 2019 (n=268). Outcome measures: We calculated incidence rates for all gastroenteritis cases per 1000 person-years at risk and per 1000 bed-days at risk. We also calculated the incidence rate of gastroenteritis outbreaks per 100 care homes per year. Results: In total 45 cases were reported during the surveillance period, equating to 133.7 cases per 1000 person-years at risk. In residents the incidence rate was 0.62 cases per 1000 bed-days. We observed seven outbreaks in all care homes included in surveillance, a rate of 76.4 outbreaks per 100 care homes per year. 15 stool samples were tested; three were positive for norovirus, no other pathogens were detected. Conclusions: We found that surveillance of infectious gastroenteritis disease in care homes based on outbreaks, the current general approach, detected a majority of cases of gastroenteritis. However, if policymakers are to estimate the burden of infectious gastroenteritis in this setting using only routine outbreak surveillance data and not accounting for non-outbreak cases, this study implies that the total burden will be underestimated.